Art culture as a component of communicative culture of the future teacher of music (Pedagogy of Higher and Secondary Education, 2007)
In the article is considered the problem of forming the communicative culture of future teachers of music by means of art culture.
Keywords: communicative culture; means offorming communicative culture; art culture; work of art